Development & automation of a novel [18F]F prosthetic group, 2-[18F]-fluoro-3-pyridinecarboxaldehyde, and its application to an amino(oxy)-functionalised Aβ peptide. (October 2016) - Morris, Olivia; Gregory, J.; Kadirvel, M.; Henderson, Fiona; Blykers, A.; McMahon, Adam; Taylor, Mark; Allsop, David; Allan, Stuart; Grigg, J.; Boutin, Herve; Prenant, Christian
Abstract: 2-[ 18 F]-Fluoro-3-pyridinecarboxaldehyde ([ 18 F]FPCA) is a novel, water-soluble prosthetic group. It's radiochemistry has been developed and fully-automated for application in chemoselective radiolabelling of amino(oxy)-derivatised RI-OR2-TAT peptide, (Aoa-k)-RI-OR2-TAT, using a GE TRACERlab FX-FN. RI-OR2-TAT is a brain-penetrant, retro-inverso peptide that binds to amyloid species associated with Alzheimer's Disease. Radiolabelled (Aoa-k)-RI-OR2-TAT was reproducibly synthesised and the product of the reaction with FPCA has been fully characterised. In-vivo biodistribution of [ 18 F]RI-OR2-TAT has been measured in Wistar rats.